PELAKSANAAN SUPERVISI OLEH PENGAWAS SEKOLAH DALAM MENINGKATKAN KOMPETENSI PROFESIONALISME GURU SD DI KECAMATAN ASTAMBUL - Yuliansyah; Rahman, Arif; Sakka, Ambo; Metroyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Teacher professionalism is a key factor in improving the quality of education; therefore, systematic guidance through academic supervision by school supervisors is essential. This study aims to describe the implementation of supervision by school supervisors in enhancing the professional competence of elementary school teachers in Astambul District. The research employed a descriptive qualitative approach through a field study. Informants were selected using purposive sampling and included school supervisors, principals, and teachers. Data were collected through in-depth interviews, non-participant observations, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation as well as member checking. The findings indicate that supervision was implemented systematically through the stages of planning, execution, and continuous coaching and follow-up. The process involved a collaborative approach between supervisors and principals, leading to improvements in lesson planning, the use of varied teaching methods and media, more effective classroom management, and enhanced teacher reflective practices. Although several challenges were identified, such as limited time, varying levels of teacher readiness, and inadequate facilities, collaborative strategies helped to address these issues. In conclusion, supervision by school supervisors plays a strategic role in enhancing teachers’ professional competence and improving the overall quality of learning.